STUDY ON THE HISTORY AND ARCHITECTURE OF THE RINZAI ZEN SECT BUDDHIST MONASTERIES IN KYÔTO - Antariksa Antariksa (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2000)
In the middle of the 14th century, the Five Temples or Five Mountains (Gozan) of Rinzai Zen sect were developed rapidly in the city of Kyôto. The ranking system of officially sponsored by Zen Buddhist monasteries were created by the Kamakura and Muromachi government. The Gozan system originally included three monasteries in Kyôto and three in Kamakura, but immediately spread to five monasteries in several cities. While the two great monasteries, are not members of the Gozan group, which belonged to the Rinka group of Rinzai Zen sect temples. The system, which corresponds to a Chinese hierarchical model, was established in Japan during the Kamakura period. The purpose of this study is to attempt to clarify the history and architecture of Rinzai Zen sect Buddhist monastery. The central functioning building of the Zen Buddhist monastery reflects the repetition, consistency, persistence, and order of the monastic ritual.